Применение нечеткой логики для принятия решений в системе автоматического контроля и слежения за нераспространением радиоактивных материалов - Забулонов, Ю.Л.; Коростиль, Ю.М.; Буртняк, В.М. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім.Г.Є.Пухова НАН України, 2010)
Is examined possibility of application of fuzzy logic vehicle for the decision of tasks in CAS of control and track after non-proliferation of radio-active materials. Inference rules are resulted for automation of process of making decision at determination of events.